Influence of Perinatal Factors on Gene Expression of IAPs Family and Main Factors of Pluripotency: OCT4 and SOX2 in Human Breast Milk Stem Cells—A Preliminary Report - Gil-Kulik, Paulina; Leśniewski, Michał; Bieńko, Karolina; Wójcik, Monika; Więckowska, Marta; Przywara, Dominika; Petniak, Alicja; Kondracka, Adrianna; Świstowska, Małgorzata; Szymanowski, Rafał; Wilińska, Agnieszka; Wiliński, Mateusz; et al. (International journal of molecular sciences, 2023)
Due to their therapeutic potential, mesenchymal stem cells are the subject of intensive research on the use of their potential in the treatment of, among others, neurodegenerative diseases or immunological diseases. They are among the newest in the field of medicine. The presented study aimed to evaluate the expression of eight genes from the IAP family and the gene regulating IAP—XAF1—in stem cells derived from human milk, using the qPCR method. The relationships between the expression of genes under study and clinical data, such as maternal age, maternal BMI, week of pregnancy in which the delivery took place, bodyweight of the newborn, the number of pregnancies and deliveries, and the time elapsed since delivery, were also analyzed. The research was carried out on samples of human milk collected from 42 patients hospitalized in The Clinic of Obstetrics and Perinatology of the Independent Public Clinical Hospital No. 4, in Lublin. The conducted research confirmed the expression of the following genes in the tested material: NAIP, BIRC2, BIRC3, BIRC5, BIRC6, BIRC8, XIAP, XAF1, OCT4 and SOX2. Moreover, several dependencies of the expression of individual genes on the maternal BMI (BIRC5, XAF1 and NAIP), the time since childbirth (BIRC5, BIRC6, XAF1 and NAIP), the number of pregnancies and deliveries (BIRC2, BIRC5, BIRC6 and XAF1), the manner of delivery (XAF1 and OCT4), preterm labor (BIRC6 and NAIP) were demonstrated. Additionally, we found positive relationships between gene expression of BIRC7, BIRC8 and XAF1 and the main factors of pluripotency: SOX2 and OCT4. This work is the first to investigate the expression of genes from the IAPs family in mother’s milk stem cells.